ANALISIS PRODUKTIVITAS KERJA KARYAWAN - Adhika, I Nyoman Resa; Astiti, Ni Putu Yeni (Insan Doktor Ekonomi Indonesia (IDEI), 2025)
Productivity refers to the ability to use available resources and infrastructure properly to achieve the best results. Labor productivity, on the other hand, refers to the ability of individuals to use resources and production variables effectively to produce services and goods. The goal is to improve the performance and efficiency of employees of an organization. The purpose of this study was to determine the effect of physical work environment, non-physical work environment, and work stress on work productivity. This study was conducted at PT. Satria Jaya based on a sample of 42 employees. The sampling method used was the census method. Data collection was carried out through observation, interviews, and questionnaires. The data analysis technique used was multiple regression analysis processed using SPSS software version 26. Based on the results of the analysis, this study shows that the physical work environment has a positive and significant effect on work productivity. The non-physical work environment has a positive and significant effect on work productivity. Work stress has a negative and significant effect on work productivity.